The Effectiveness of Adaptive Coping Strategies for Work Stress: A Meta-Analysis - Yoneta Wamea; Nompo, Rifki Sakinah (Open Access Indonesian Journal of Medical Reviews, 2024)
Work stress is a significant global health problem, negatively impacting employee physical and mental health as well as company productivity. Adaptive coping strategies can be an important intervention in reducing the negative effects of work stress. This research aims to evaluate the effectiveness of adaptive coping strategies in reducing work stress and improving employee well-being through meta-analysis. A systematic literature search was conducted on electronic databases (PubMed, PsycINFO, Scopus, Web of Science) to identify randomized controlled studies (RCTs) published between 2018 and 2024. Studies that met the inclusion criteria (working adult participants, adaptive coping strategy interventions, outcomes work stress and/or well-being) data were extracted and analyzed using a random effects model. Twenty-five RCTs involving 4,852 participants met the inclusion criteria. Meta-analysis showed that adaptive coping strategies significantly reduce work stress (pooled effect size = -0.45, 95% CI [-0.58, -0.32], p < 0.001) and improve well-being (pooled effect size = 0.38, 95% CI [0.25, 0.51], p < 0.001) compared with the control group. Subgroup analyzes revealed that adaptive coping strategies focused on problem-solving, social support, and relaxation had the greatest effectiveness. Adaptive coping strategies are effective in reducing work stress and improving employee well-being. These findings support the implementation of adaptive coping strategies as an occupational health intervention to reduce the negative impact of work stress.